2010
DOI: 10.1029/2009ja015136
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the solar quiet geomagnetic field variation linked to the Earth's magnetic field secular variation and increasing concentrations of greenhouse gases

Abstract: Long‐term trends in solar quiet geomagnetic field variation (Sq) are studied in connection to the Earth's magnetic field secular variations and increasing greenhouse gas concentrations. Sq is mainly caused by ionospheric current systems that flow in the E region and depends, among other variables, on the ionospheric conductivities. These conductivities in turn depend on the Earth's main magnetic field (B) and the electron concentration in the E region, for which foE is a measure of its peak value. Since B show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 41 publications
1
46
1
Order By: Relevance
“…They found significant trends (on the order of 10 −4 nT per day) in the residual data at some stations, but the trends were not always consistent among the stations. Elias et al (2010), using a similar technique, showed significant trends in the residual Sq amplitude at Apia (13.8°N, 171.8°W), Fredericksburg (38.2°N, 77.3°W), and Hermanus (34.4°S, 19.2°E) during 1960Hermanus (34.4°S, 19.2°E) during -2001. The trends in the residual Sq amplitudes were found to be all positive: 2.2 × 10 −4 nT/day, 1.3 × 10 −4 nT/day, and 2.1 × 10 −4 nT/day, respectively.…”
Section: Long-term Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…They found significant trends (on the order of 10 −4 nT per day) in the residual data at some stations, but the trends were not always consistent among the stations. Elias et al (2010), using a similar technique, showed significant trends in the residual Sq amplitude at Apia (13.8°N, 171.8°W), Fredericksburg (38.2°N, 77.3°W), and Hermanus (34.4°S, 19.2°E) during 1960Hermanus (34.4°S, 19.2°E) during -2001. The trends in the residual Sq amplitudes were found to be all positive: 2.2 × 10 −4 nT/day, 1.3 × 10 −4 nT/day, and 2.1 × 10 −4 nT/day, respectively.…”
Section: Long-term Variationmentioning
confidence: 99%
“…The trends in the residual Sq amplitudes were found to be all positive: 2.2 × 10 −4 nT/day, 1.3 × 10 −4 nT/day, and 2.1 × 10 −4 nT/day, respectively. Elias et al (2010) showed that these positive trends can be explained in part as the effect of long-term changes in the ionospheric conductivities. However, the observed long-term trends in the residual Sq amplitudes were greater than those expected from the conductivity changes; thus, other contributions such as CO 2 might also play a role.…”
Section: Long-term Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational evidence has confirmed many of these predictions, at least in a qualitative sense: the global mean neutral density at fixed heights of 250-400 km has been decreasing (Keating et al 2000;Emmert et al 2004;Emmert & Picone 2011), the ion temperature, which is closely coupled to the neutral temperature, has been decreasing at several stations (Donaldson et al 2010;Zhang et al 2011;Zhang & Holt 2013), and at many stations decreasing trends in the heights of the maximum electron density of the ionospheric E and F 2 layers have been found (Bremer 1992(Bremer , 2008Ulich & Turunen 1997;Jarvis et al 1998;Bremer et al 2012). It has also been suggested that the changes in the ionosphere arising from increased greenhouse gases could be responsible, at least partly, for observed longterm changes in the daily amplitude of magnetic perturbations associated with the solar quiet (Sq) current system flowing in the low-to mid-latitude dayside ionosphere (Torta et al 2009;Elias et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…ñ ñîëíå÷íîé ðàäèàöèåé , ÷èñëàìè Âîëüôà, êîñìè÷åñêèìè ëó÷àìè, ïðè-çåìíîé òåìïåðàòóðîé è äðóãèìè ïàðàìåòðàìè îïèñàíû âî ìíîãèõ ñòàòüÿõ (ñì., íàïðèìåð, [Cliver et al, 1998;Svensmark, 1998;Bard et al, 2000;Crowley, 2000;Svensmark, 2000;Solanki et al, 2000Solanki et al, , 2002Foukal, 2002;Carslaw et al, 2002;Kristjansson et. al., 2004;Shea, Smart, 2004;Usoskin et al, 2003Usoskin et al, , 2005Foukal et al, 2006;Bard, Frank, 2006;El-Borie, Al-Thoyaib, 2006;Valev, 2006;Brohan et al, 2006;Scafetta, West, 2006;Lockwood, Fröhlich, 2007;Vieira, da Silva, 2008;Elias et al, 2010;Mufti, Shah, 2011;Stauning, 2011;Love et al, 2011;Souza Echer et al, 2011Lockwood, 2012].…”
Section: ïðåäñòàâëåíî ÷ëåíîì ðåäêîëëåãèè â í øóìàíîìmentioning
confidence: 99%